Experimental and analytical study on structural performance of reinforced lightweight geopolymer composites panels - Li, Zhixing; Chen, Wensu; Hao, Hong; Xu, Cheng; Pham, Thong (2023)
Various lightweight panels such as autoclaved aerated concrete (AAC) panels have been widely used in the prefabricated construction. With the growing demand for eco-friendly building materials, geopolymer as cementitious material has been extensively studied. A novel ambient-cured lightweight geopolymer composite (LGC) with expanded polystyrene (EPS) was recently developed by the authors and demonstrated sound static and dynamic mechanical properties. In this study, a new lightweight reinforced panel made of LGC is proposed for prefabricated structures. Five full-scale panels, including one AAC panel and four LGC panels with different configurations, were prepared and tested under four-point bending to investigate the effects of panel thickness and reinforcement configuration on the structural performance. The test results showed that the LGC panels demonstrated better structural performance, with the characteristic ultimate bending capacity 57%-110% higher than that of the corresponding AAC panel. An analytical study was also conducted, and empirical formulae were proposed to predict the ultimate bending capacity of LGC panels.